2011
DOI: 10.1186/1471-2458-11-834
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between commuting and health outcomes in a cross-sectional population survey in southern Sweden

Abstract: BackgroundThe need for a mobile workforce inevitably means that the length of the total work day (working and traveling time) will increase, but the health effects of commuting have been surprisingly little studied apart from perceived stress and the benefits of physically active commuting.MethodsWe used data from two cross-sectional population-based public health surveys performed in 2004 and 2008 in Scania, Sweden (56% response rate). The final study population was 21, 088 persons aged 18-65, working > 30 h/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
145
6
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(167 citation statements)
references
References 32 publications
(58 reference statements)
10
145
6
6
Order By: Relevance
“…Irrespective of what mode of transport a person use, commuting also takes time from other social activities that are beneficial for our well-being (Dolan and White 2007) and has also been shown to correlate with health problems (Hansson 2011) and low levels of SWB (Stutzer and Frey 2008;Killingsworth and Gilbert 2010). However, Olsson et al (2013) found that feelings during commutes are predominantly positive or neutral and speculate that the commuting offers buffer time between work and private spheres of life.…”
Section: Commutingmentioning
confidence: 99%
“…Irrespective of what mode of transport a person use, commuting also takes time from other social activities that are beneficial for our well-being (Dolan and White 2007) and has also been shown to correlate with health problems (Hansson 2011) and low levels of SWB (Stutzer and Frey 2008;Killingsworth and Gilbert 2010). However, Olsson et al (2013) found that feelings during commutes are predominantly positive or neutral and speculate that the commuting offers buffer time between work and private spheres of life.…”
Section: Commutingmentioning
confidence: 99%
“…For car commuting, the relationships were concave downward or flat, with increasing subjective health complaints up to 30-60 min (ORs ranging from 1.2-1.4), and lower ORs in the >60 min category. 25 A number of limitations of our study need to be noted. We drew on cross-sectional data, which does not allow inferences of causality from observed associations.…”
mentioning
confidence: 92%
“…Furthermore, commuting has been shown to be associated with increased heart rate and blood pressure (Novaco et al, 1979;Schaeffer et al, 1988). Further, commuting translates into shorter sleeping times and sleep disorders (Costa et al, 1988;Walsleben et al, 1999;Hansson et al, 2011), a lower social capital and participation (Mattisson et al, 2015), which has in turn been associated with health outcomes (Putnam, 2000;Lindström, 2004;Besser et al, 2008), negative mood (Gulian et al, 1989), emotional arousal (Hennessy and Wiesenthal, 1997), lower well-being and life satisfaction (Stutzer and Frey, 2008;Roberts et al, 2011;Olsson et al, 2013) as well as higher levels of workplace aggression (Hennessy, 2008), poor concentration levels (Matthews et al, 1991) and a higher risk of mortality (Sandow et al, 2014).…”
mentioning
confidence: 99%